Resource consumption trade-off for reducing hotspot migration in modern data centres. (24th September 2021) - Berrima, Mouhebeddine; Louhichi, Walid; Rajeb, Narjes Ben
Virtual machine migration is a basic mechanism to implement dynamic resource management such as resource restraints management, physical machine consolidation, and load balancing. These are necessary to reduce the operational costs of cloud providers and thus increase their business profits. However, the migration operations interrupt the execution of user services leading to a degradation of service performance. In this paper, we propose a virtual machine placement algorithm significantly reducing the number of hotspot migrations performed to manage resource restraints. The reduction overhead is an extra use of resources depending on some cloud environment settings. The proposed algorithm is designed for dynamic modern data centres housed in truck-towed containers, and thus can be relocated at sites where utilities for electricity are cheaper. Through empirical evaluation, we analyse the trade-off between hotspot migrations and resource consumption according to different parameters. Simulation results affirm that our algorithm is more efficient in data centres with a greater degree of physical machine virtualisation. Moreover, compared to a proactive migration algorithm, our algorithm promotes better the reduction of hotspot migrations in high dynamic data centres.